RAZLIKE SOCIOLOŠKIH INDIKATORA UČENICA I UČENIKA GIMNAZIJA - Danijela Bonacin; Stipe Blažević; Franjo Lovrić (Sport Mont, 2009)
Problem of this research was determination of differences in sociological struc- ture indicators of male and female pupils connected with their institutional, residential, sanction and management status. An idea was to investigate and offer adequate conclu- sions needed for several educational and other institutions for easier approach to such population. In this research we surround two samples of entities: 647 female and 400 male students of grammar school described with 52 indicators. Data were collected with questionnaire. After normalization and elementary statistics data were processed with Data were processed by normalization, elementary statistics, and for this work purposes it was Analysis of variance for independent samples applied for group differences inve- stigation. Results have shown that girls be rather stay at home, try to ensure some kind of security and much more altruists then male students. Male students, on the contrary, rather move around, follow fashion trends, manage in society and school learning and finally want a reward for their activities. Those results explain existing of traditional acceptance of male-female relationships with woman oriented toward house and man toward their goals. It is a real question of natural measure of such position and maybe it is just a traditional surround position product. It is suggested detail investigation and confirmation of such results in the future.